Manajemen Asuhan Kebidanan Continuety Of Care (COC) Pada Ibu Hamil Dengan Jarak Kehamilan < 2 Tahun, Bersalin, Bayi Baru Lahir, Nifas Dan Keluarga Berencana Pada Ny. L Di Klinik Erlina Wati Kecamatan Hinai , Kabupaten Langkat Provinsi Sumatera Utara - Seri Wahyuni; Nurgelang Hasibuan; Nelly Gustina; Nurlina S; Meylina Br Siboro-boro; Br Sembiring, Isyos Sari; Yenni Kurniawati (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
The process of pregnancy, childbirth and the puerperium is a natural stage of human reproduction, but we must be aware of things that can endanger the health of the mother and baby. Purpose: This study provides pregnant women, childbirth, newborns, postpartum and family planning at the Erlina Wati Maternity Clinic during the second trimester of pregnancy until the family planning period at the Erlina Wati Maternity Clinic, Hinai District, North Sumatera Regency in 2022. Method: used in this case study uses a qualitative research method that is descriptive with behavior, perceptions, motivations, actions using a case study design. Data analysis with descriptive analysis which is in accordance with midwifery care standards and progress notes with SOAP at the Erlina Wati Maternity Clinic, Hinai District, North Sumatera Regency in 2022. Result: of the case studies that have been conducted on Mrs. L during pregnancy in the second trimester is normal, normal delivery, normal 40 days postpartum, normal 28 days neonate, contraceptive use Mal. Conclusion: in the case study from the second trimester of pregnancy to the period of family planning, objective and objective data were not found complaints and abnormalities that lead to pathological conditions, from beginning to end there were no emergency problems. Implementation is carried out according to the diagnosis. Suggestion: health workers are able to provide comprehensive and continuous care so as to prevent maternal and child deaths.